1998
DOI: 10.1128/mcb.18.5.2596
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing Variants of IκBβ Establish Differential NF-κB Signal Responsiveness in Human Cells

Abstract: To release transcription factor NF-B into the nucleus, the mammalian IB molecules IB␣ and IB␤ are inactivated by phosphorylation and proteolytic degradation. Both proteins contain conserved signal-responsive phosphorylation sites and have conserved ankyrin repeats. To confer specific physiological functions to members of the NF-B/Rel family, the different IB molecules could vary in their specific NF-B/Rel factor binding activities and could respond differently to activation signals. We have demonstrated that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 48 publications
1
51
0
Order By: Relevance
“…3C). Although two hybridization signals of equal intensity appear due to alternative splicing of the I B-␤ pre-mRNA [39,52], neither band is induced by sodium butyrate. These results suggest that sodium butyrate may inhibit the nuclear translocation of NF-B by inducing the protein expression of I B-␤ via a mechanism independent of steady-state mRNA levels.…”
Section: Sodium Butyrate Induces the Protein Expression Of I B-␤ But mentioning
confidence: 99%
“…3C). Although two hybridization signals of equal intensity appear due to alternative splicing of the I B-␤ pre-mRNA [39,52], neither band is induced by sodium butyrate. These results suggest that sodium butyrate may inhibit the nuclear translocation of NF-B by inducing the protein expression of I B-␤ via a mechanism independent of steady-state mRNA levels.…”
Section: Sodium Butyrate Induces the Protein Expression Of I B-␤ But mentioning
confidence: 99%
“…Upon stimulation, IκBβ1 is rapidly degraded whereas IκBβ2 is only weakly degraded which serves to limit the activity of NFκB. 36 Thus, a balance between these two isoforms, in addition to the function of other IκB proteins, enables precise regulation of NFκB activity.…”
Section: Resultsmentioning
confidence: 99%
“…4A). 36 The two proteins differ in their C-termini, with the smaller protein, IκBβ2, being produced by an intron retention event. The SpliceArray indicated that overexpression of SRrp86 stimulated removal of this intron and therefore production of the larger protein, IκBβ1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypophosphorylated IB␤ can bind NF-B without masking its nuclear localization signal (32), thus acting as a chaperone for NF-B nuclear entry and preventing its sequestration by IB␣. Recently, two isoforms of IB␤ that differ in their C-terminal PEST domain as a consequence of alternative splicing have been identified in human cells (34). The larger protein, approximately 43 kDa, is homologous to the murine IB␤, whereas the 41-kDa form is unique to human cells.…”
Section: Hiv-1mentioning
confidence: 99%